2018
DOI: 10.1039/c8ra02803f
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided isolation and identification of anticancer and antioxidant compounds from Gynostemma pentaphyllum (Thunb.) Makino

Abstract: Gynostemma pentaphyllum (Thunb.) Makino is a medicinal and edible plant in China whose buds and leaves are used for making a popular kind of tea drink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…The experiment was carried out according to the method of Wang with slight modifications. 21 One hundred microliters of different concentrations of the solution to be tested (0.20, 0.40, 0.60, 0.80, 1.00 mL mL −1 DES extract, 70% methanol extract, 70% ethanol extract, 100% ethanol extract, and 1 mmol per L VC solution) were placed in a test tube, and 0.1 mL of 0.2 mol per L phosphate buffer (pH = 6.6) and 0.1 mL of 1% K 3 Fe(CN) 6 were mixed well and reacted at 50 °C for 20 min. Then, 0.1 mL of 10% trichloroacetic acid solution was added, mixed and centrifuged for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was carried out according to the method of Wang with slight modifications. 21 One hundred microliters of different concentrations of the solution to be tested (0.20, 0.40, 0.60, 0.80, 1.00 mL mL −1 DES extract, 70% methanol extract, 70% ethanol extract, 100% ethanol extract, and 1 mmol per L VC solution) were placed in a test tube, and 0.1 mL of 0.2 mol per L phosphate buffer (pH = 6.6) and 0.1 mL of 1% K 3 Fe(CN) 6 were mixed well and reacted at 50 °C for 20 min. Then, 0.1 mL of 10% trichloroacetic acid solution was added, mixed and centrifuged for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Nghiên cứu tác dụng hạ cholesterol máu cho thấy dịch chiết nước của cây Giảo cổ lam có tác dụng giảm 71% lượng cholesterol trong chuột thí nghiệm [19]. Giảo cổ lam có tác dụng tăng đáp ứng miễn dịch trên chuột ở cả hai mô hình gây ức chế miễn dịch bằng cyclophosphamid và tia xạ [20]. Chiết xuất tự nhiên của Giảo cổ lam đã được nghiên cứu như một chất chống ung thư mạnh chống lại một số loại tế bào ung thư [21], [22].…”
Section: Bàn Luậnunclassified
“…Previous studies have revealed that G. pentaphyllum shows antioxidant, anti‐inflammatory, neuroprotective, and anti‐cancer properties (Xie et al, 2010). In particular, gypenoside L, the main active constituent in G. pentaphyllum , is known to have a remarkable antioxidant capacity (Wang et al, 2018). Despite its beneficial effects on muscle fatigue, as reported based on in vitro and in vivo studies (Kim, Jung, Jeon, Kim, Hong, et al, 2020; Kim, Jung, Jeon, Kim, Oh, et al, 2020), there have been no clinical trials on its effects on exercise‐induced changes in blood and biochemical parameters of fatigue and physical performance.…”
Section: Introductionmentioning
confidence: 99%